A study on ISO9001: 2000 quality management system (QMS) in Mahkamah Rendah Syariah, Ipoh, Perak: addressing the effectiveness of quality management system (on the organization), conformity to customers' and application of regulatory requirement / Adham Jamalullail Ibrahim, Zabedah Mohd Salleh and Haliza Idris - Ibrahim, Adham Jamalullail; Mohd Salleh, Zabedah; Idris, Haliza (2008)
ISO 9000 standards help to ensure the organization follow and implement specific rules and well documented procedures and objectives which will describe how operations in an organization must be conducted. By doing so, these procedures are meant to guarantee that the products or services of an organization are in accordance with customer satisfaction. ISO benefit can be divided into internal benefit which comprise of processes and structure of the organization and external benefit which concerning the organization in relation to its environment. The idea of introduction of quality management services is to promote the best quality services which ultimately lead to satisfaction of customer. The nature and intensity of motivations behind a decision to adopt the ISO 9000 standard play a key role in the success of the implementation process and the degree of customer's satisfaction. This study examines the relationship between ISO 9001:2000 effectiveness on application of regulatory requirement and conformity to customer satisfaction. It intends to look for possible answer and give solid evidence to the idea of introduction of quality management services in public sector particularly in judiciary department to promote the best quality services which ultimately lead to customer's satisfaction.